THE MODELS FOR LAND USE DEVELOPMENT WITH THE ACCELERATION OF URBANIZATION IN URBAN CHINA - A CASE STUDY OF PEARL RIVER DELTA METROPOLIS - Wu Zhigang; Zhou Suhong; Feng Changchun (European Regional Science Association (ERSA), 2005)
There appears bran-new models of land use development which is not entirely in accord with national policy in China, especially in the rapid urbanization zone. It results from the conflicts between the active two-system of land use policy and the rapid development of society and economy in these areas. Although it disobeys the national law of land use in some aspects, this phenomenon reveals the irrationality on the active land policy, which has to be reformed for the urban sustainability. After summarizing and analysing the typical models of land use development of the rapid urbanization areas in the Pearl-river Delta metropolitans, the paper gives some conclusions and some suggestions for land policy reform in the future.
Keywords: 330